Randomized clinical trial of enhanced recovery versus standard care after laparoscopic sleeve gastrectomy. Issue 4 (21st January 2013) - Lemanu, D. P.; Singh, P. P.; Berridge, K.; Burr, M.; Birch, C.; Babor, R.; MacCormick, A. D.; Arroll, B.; Hill, A. G.
Abstract: Background: Optimized perioperative care within an enhanced recovery after surgery (ERAS) protocol is designed to reduce morbidity after surgery, resulting in a shorter hospital stay. The present study evaluated this approach in the context of sleeve gastrectomy for patients with morbid obesity. Methods: Patients were allocated to perioperative care according to a bariatric ERAS protocol or a control group that received standard care. These groups were also compared with a historical group of patients who underwent laparoscopic sleeve gastrectomy at the same institution between 2006 and 2010, selected using matched propensity scores. The primary outcome was median length of hospital stay. Secondary outcomes included readmission rates, postoperative morbidity, postoperative fatigue and mean cost per patient. Results: Of 116 patients included in the analysis, 78 were allocated to the ERAS (40) or control (38) group and there were 38 in the historical group. There were no differences in baseline characteristics between groups. Median hospital stay was significantly shorter in the ERAS group (1 day) than in the control (2 days; P < 0·001) and historical (3 days; P < 0·001) groups. It was also shorter in the control group than in the historical group ( P = 0·010). There was no difference in readmission rates, postoperative complications or postoperative fatigue. The mean cost per patient was significantly higher in the historical group than in the ERAS ( P = 0·010) and control ( P = 0·018) groups. Conclusion: The ERAS protocol in the setting of bariatric surgery shortened hospital stay and was cost‐effective. There was no increase in perioperative morbidity. Registration number: NCT01303809 (http://www.clinicaltrials.gov). Copyright © 2013 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd. Abstract : More evidence that enhanced recovery is beneficial